Analyzing efficiency of optical and THz infrared thermography in nondestructive testing of GFRPs by using the Tanimoto criterion. (January 2021) - Chulkov, А.О.; Sommier, A.; Pradere, C.; Vavilov, V.P.; Siddiqui, A.O.; Prasad, Y.L.V.D.
Abstract: This study has illustrated the potentials of optical and THz infrared thermography in the identification of inserts of different nature in glass fiber reinforced polymer. The inspection efficiency has been comparatively evaluated by applying the Tanimoto criterion. The best test procedure has proven to be one-sided stationary thermal nondestructive testing (TNDT) implementing optical heating with Xenon lamps (Tanimoto criterion 87%). Close values of the Tanimoto criterion have been achieved by using the optical and THz line-scanning procedures. A more subjective evaluation of test procedures has been performed by comparing eight parameters of test performance. The line-scanning TNDT procedure implementing optical heating with halogen lamps seems to be optimal in practical applications.